A concept analysis of the patient experience - Tanja Avlijas; Janet Squires; Michelle Lalonde; Chantal Backman (The Beryl Institute, 2023)
Patient experience, an essential indicator of quality patient care, is of increasing importance to hospitals that want to improve and maintain strong patient experience metrics to remain competitive in the business of healthcare. The aim of this study was to clarify the concept of the patient experience by identifying its existing definitions, methods of measurement, and underlying themes and attributes, to differentiate it from similar concepts and propose an operational and theoretical definition to guide valid and reliable development of future assessment tools. Walker and Avant's eight-step methodology served as the framework for this concept analysis. A literature search, using seven databases and one search engine, was conducted of existing literature published any time up until September 2021. The search identified 19,447 references of which 436 articles and organizational websites were included. Twenty attributes (n= 20) were found to define the patient experience: (1) communication; (2) respect for patients; (3) information and education; (4) patient-centered care; (5) comfort and pain; (6) discharge from hospital; (7) hospital environment; (8) professionalism and trust; (9) clinical care and staff competency; (10) access to care; (11) global ratings (12) medication; (13) transitions and continuity; (14) emotional dimension; (15) outcomes; (16) hospital processes; (17) safety and security; (18) interdisciplinary team; (19) social dimension; and, (20) patient dependent features. The proposed definition of the patient experience is: "Patient experience is the combination of external and internal hospital processes, patient-centered attributes, patient-staff and staff-staff interactions during all episodes of care." Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Policy%20%26%20Measurement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.